Efecto de los factores de transcripción SRY y CREB en la regulación del promotor CATSPER 1 de humano - Hernández Reyes, Adriana (Universidad Autónoma Metropolitana, 2012)
CATSPER 1 gene encodes for a protein- forming CatSper channel, a cationic channel that allows calcium entry, essential for motility of sperm flagellum, whose expression is exclusive of male germ cells. The analysis of transcription factors that regulate human CATSPER 1 promoter is relevant for understanding male fertility and contraception. If the CATSPER 1 gene is expressed during sperm differentiation, might be that transcription factors SRY and CREB regulate its transcription. The aim is the CATSPER 1 promoter characterization based on its basal transcriptional activity and the analysis of SRY and CREB participation on its regulation. CATSPER 1 promoter was assessed throughout sequential deletions on 5 ́end, HEK 293 cell transfection and luciferase assays to determine transcriptional activity. In the same manner, the effect of SRY overexpression on CATSPER 1 promoter transcriptional activity was analyzed. In addition, the binding of transcriptional factors to specific sites in the promoter was tested by Electrophoretic Mobility Shift Assay (EMSA). The deletion of distant SRY and CREB binding sites increases transcriptional activity, suggesting that such transcriptional factors are repressors in these sites. On the other hand, the over - expression of SRY increases transcriptional activity on proximal binding sites to the Transcription Start Site (TSS). The specific interaction of SRY and CREB with CATSPER 1 promoter is still under study due to its complexity. SRY and CREB participate as repressors in the transcriptional regulation of human CATSPER 1 promoter.; CATSPER 1 es un gen que descodifica para una de las proteínas del canal CatSper permeable a calcio que es indispensable para la movilidad flagelar del espermatozoide, y su expresión es exclusiva de células germinales masculinas. Es relevante analizar los factores de transcripción (FT) que regulan al promotor del gen CATSPER 1 de humano, ya que éste es importante para la fertilidad y la anticoncepción masculina. Por lo que si el gen CATSPER 1 se expresa durante la diferenciación del espermatozoide, se espera que FT como CREB y SRY presentes en la espermatogénesis regulen su expresión. El objetivo es la caracterización molecular de la actividad transcripcional del promotor CATSPER 1 y la participación de los FT SRY y CREB en su regulación. Se caracterizó la actividad transcripcional del promotor mediante la deleción secuencial del extremo 5’, transfección celular en HEK 293 y medición por quimioluminiscencia del gen reportero de luciferasa. Sobre- expresión del FT SRY y su efecto en el promotor. Evaluación de la unión de FT a sitios del promotor por EMSA. La deleción en el promotor de los sitios SRY y CREB, lejanos del inicio de la transcripción, incrementa la actividad transcripcional, lo que sugiere que los FT actúan como represores en estos sitios. Por otra parte la sobreexpresión de SRY produce el incremento de la actividad transcripcional en sitios cercanos al inicio de la transcripción. Se sigue determinando la unión de SRY y CREB en sitios específicos del promotor. SRY y CREB son reguladores negativos del gen CATSPER 1 de humano.